2013
DOI: 10.1038/ejcn.2013.155
|View full text |Cite
|
Sign up to set email alerts
|

Potential renal acid load and the risk of renal stone formation in a case–control study

Abstract: A PRAL in diet and a reduced consumption of vegetables are associated with an increased risk of calcium renal stone formation. In renal stone formers consumption of plant foods should be encouraged in order to counterbalance the acid load derived from animal-derived foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 18 publications
0
21
1
5
Order By: Relevance
“…As the demand for acid elimination increases, the kidney plays other adaptive responses that may culminate in an increased risk of CKD. As previously mentioned, a diet rich in fruits and vegetable might reduce the formation of kidney stones [18] and CKD risk [27,29]. Since low serum bicarbonate levels are an independent predictor of CKD progression, the high consumption of fruit and vegetables is also associated with a reduced progression of early CKD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the demand for acid elimination increases, the kidney plays other adaptive responses that may culminate in an increased risk of CKD. As previously mentioned, a diet rich in fruits and vegetable might reduce the formation of kidney stones [18] and CKD risk [27,29]. Since low serum bicarbonate levels are an independent predictor of CKD progression, the high consumption of fruit and vegetables is also associated with a reduced progression of early CKD.…”
Section: Discussionmentioning
confidence: 99%
“…If there is an excessive consumption of acid precursor foods, to the detriment of those precursors of bases, volubility of the acid-base balance occurs [2,3,17]. If this acid-base balance disorder occurs in a prolonged and chronic way, low-grade metabolic acidosis may become significant and predispose to diseases [18,19,20,21]. …”
Section: Diet-induced Acidosismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the formation of calcium stones can be favored by reduced fluid intake, excessive consumption of meat, a low intake of milk and dairy products and insufficient consumption of vegetables. Not necessarily all of these factors must coexist simultaneously, as it is the sum of the effects of each of them to determine the risk of kidney stones (14). For this reason, it is not surprising to observe different dietary patterns in patients living in different countries where the diet may be different due to geographical, cultural and socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case-control study, 123 renal calcium stone formers were compared with age-and sex-matched controls with regard to the potential renal acid load calculated from dietary records. 36 It was shown that potential renal acid load in diet and reduced consumption of vegetables were associated with occurrence of calcium nephrolithiasis. As mentioned, dietary acid load primarily is a result of sulfur containing animal protein ingestion.…”
Section: Dietary Salt and Hypertensionmentioning
confidence: 99%